Factors Affecting E-Satisfaction An Experience from Germany - Shahriar Azizi; Amirnima Negahdari (Journal of Information Technology Management)
The first and most important principle of marketing is focusing on the customer needs and wants, because regardless of that, companies will not be able to survive in today's competitive environment. These days, companies know that providing products and services according to customer needs and demands, is an important competitive advantage to gain more sales and benefit, so identifying customer needs and demands, and adopting appropriate strategies for supplying customers' desires are the most important activities in competitive markets. Considering the competitive environment in e-commerce and importance of focus on customer expectations in electronic markets, this study has been aimed to identify and prioritize the factors affecting customer satisfaction in electronic commerce. For data collection and final testing of the E-SAT model, questionnaire was designed and distributed between 221 people in Germany. Collected data was analyzed by SPSS software. The research model had found out that from six main factors and 25 sub factors, six factors and 17 sub factors affect satisfaction in online shopping. Also in this study, the type of goods, prices of purchased goods and age range of online buyers are investigated.